Future plans of veterinary graduates in Germany in 2023: an online survey - Riemann, Mira Elisabeth; Hoedemaker, Martina; Jensen, Katharina Charlotte (Frontiers in Veterinary Science, 2025)
IntroductionIn Germany, as in other countries, a shortage of veterinarians is threatening the health and welfare of pets and livestock. Against this background, the aim of this study was to find out what plans veterinary graduates have after their studies, what field they want to work in and whether their career aspirations change during their studies. In addition, it was investigated whether the factors of gender, origin (urban/rural), and animal ownership before studying were associated with future planning/decision-making.Materials and methodsWith the help of an online survey, German graduates of veterinary medicine from the class of 2023 were interviewed. Responses from 157 people were analyzed, which corresponds to a response rate of around 17%.ResultsThe results of this study show that almost half of the participants (n = 76; 48%) would like to work in a practice directly after graduation and 63% of respondents (n = 98) saw themselves working in a practice in 5 years’ time. The field of small animal medicine was the most strongly represented, followed by equine medicine. Only 42% of participants (n = 66) saw themselves in the same veterinary field in the future as they had aspired to before their studies. Neither gender nor origin were associated with future planning. However, the husbandry of certain animal species before studying was significantly associated with the field in which the respondents wanted to work later.DiscussionThese results provide an initial basis for estimating how many veterinarians enter the respective fields and should be taken into account when discussing changing the admission requirements of universities of veterinary medicine to attract more young people to a certain animal field or a certain region of Germany.